Molecular detection of viruses from hand, foot, and mouth disease patients in Seri Kembangan, Selangor, Malaysia - Beh, Poay Ling (2014)
Hand, foot, and mouth disease (HFMD) is a common acute viral infection that affects infants and young children. The major causative agents of HFMD are enterovirus 71 (EV71) and coxsackievirus A16 (CVA16). Recently, HFMD cases that are caused by coxsackievirus A6 (CVA6) were reported in neighboring countries. The signs and symptoms of the infection are fever, mouth/throat ulcers, rashes and vesicles in palms and soles. Patients that were infected by EV71 might have serious and fatal complications, such as meningitis, encephalitis and acute flaccid paralysis. EV71 outbreaks that caused fatalities were reported in Sarawak and Peninsular Malaysia since 1997. Fatal cases caused by EV71 were reported in Selangor during the outbreaks. Although fatalities reported in Selangor, the data of HFMD in this area was limited. The purposes of this study were; to detect and identify the HFMD viruses from the patients below 12 years old who presenting clinical case definitions of HFMD in Seri Kembangan, Selangor; and to describe the demographic data and clinical presentations of the patients with the viral agents. A total of 28 specimens were collected from patients who presented with clinical case definitions of HFMD. The specimen collection period was from December 2012 until July 2013. The HFMD viruses were directly detected from specimens by using seminested reverse transcription-polymerase chain reaction (snRT-PCR). The positive snRT-PCR products were sequenced and phylogenetic trees were constructed. Virus isolation were performed on positive snRT-PCR specimens and reconfirmed by snRT-PCR. Among 28 specimens, 12 were positive in snRT-PCR. Based on sequencing results, seven of them were CVA6, two CVA16, and three EV71. According to phylogenetic analysis, EV71 strains were classified as sub-genotypes B5; CVA16 strains were identified sub-genotypes B2b and B2c; CVA6 strains were closely related to strains in Taiwan and Japan. In virus isolation, only one of 12 positive snRT-PCR specimens was successfully isolated from the cell culture, which was CVA16. The relationship between demographic data and clinical presentations with viral agents were studied. In conclusion, HFMD in Seri Kembangan, Selangor were caused by different genotypes of viruses, which were CVA6, CVA16 and EV71.